Structure and Intensity Based Approach in Credit Risk Models: A Literature Review - Adithi Ramesh; C.B Senthil Kumar (International Journal of Economics and Financial Issues, 2017)
Credit Risk modeling has been a subject of considerable research interest for finance and statistical researchers. The quantification of credit risk by assigning measurable and comparable numbers to the likelihood of default or spread risk is a major frontier in modern finance. In this paper we provide a literature review of credit risk models including both structural and intensity based approaches. Our focus is placed on probability of default and hazard rate of time to default.